Dehydrin MsDHN1 improves aluminum tolerance of alfalfa (Medicago sativa L.) by affecting oxalate exudation from root tips. (25th August 2021) - Lv, Aimin; Wen, Wuwu; Fan, Nana; Su, Liantai; Zhou, Peng; An, Yuan
SUMMARY: A SK3 ‐type dehydrin MsDHN1 was cloned from alfalfa ( Medicago sativa L.). Its function and gene regulatory pathways were studied via overexpression and suppression of MsDHN1 in alfalfa seedlings or hairy roots. The results showed that MsDHN1 is a typical intrinsically disordered protein that exists in the form of monomers and homodimers in alfalfa. The plant growth rates increased as a result of MsDHN1 overexpression ( MsDHN1 ‐OE) and decreased upon MsDHN1 suppression ( MsDHN1‐ RNAi) in seedlings or hairy roots of alfalfa compared with the wild‐type or the vector line under Al stress. MsDHN1 interacting with aquaporin (AQP) MsPIP2;1 and MsTIP1;1 positively affected oxalate secretion from root tips and Al accumulation in root tips. MsABF2 was proven to be an upstream transcription factor of MsDHN1 and activated MsDHN1 expression by binding to the ABRE element of the MsDHN1 promoter. The transcriptional regulation of MsABF2 on MsDHN1 was dependent on the abscisic acid signaling pathway. These results indicate that MsDHN1 can increase alfalfa tolerance to Al stress via increasing oxalate secretion from root tips, which may involve in the interaction of MsDHN1 with two AQP. Significance Statement: Dehydrin MsDHN1 is a typical intrinsically disordered protein that exists in the form of monomers and homodimers. MsDHN1 increased alfalfa tolerance to Al stress by interacting with aquaporins and increasing oxalate secretion.